It's All about Race: How State Legislators Respond to Immigrant Constituents. (September 2018) - Gell-Redman, Micah; Visalvanich, Neil; Crabtree, Charles; Fariss, Christopher J.
How do elected representatives respond to the needs of immigrant constituents? We report the results of a field experiment on U.S. state legislators in which the nativity, likelihood of voting, and race/ethnicity of a hypothetical constituent are independently manipulated. The experimental design allows us to contribute new insights by isolating the various elements that may impede the connection between immigrants and elected representatives. Moreover, we explore racial/ethnic identities beyond black and white by including Latino and Asian aliases. Contrary to expectations, nativity and voting status do not affect response rates. Instead, legislator behavior appears to be driven by racial/ethnic bias. Whites benefit from the highest response rate, while blacks, Hispanics, and Asians all receive lower rates, respectively. This bias follows a partisan logic. The low response rate for Hispanic constituents comes primarily from Republican legislators, whereas Asians experience bias from representatives of both parties. We argue that this difference may result from Hispanic identity sending a stronger signal about partisan affiliation, or from a prejudicial view of Asians as outsiders. In this last interpretation, rather than the model minority, Asians become the excluded minority.